Mucocutaneous adverse events to immune checkpoint inhibitors - Muhaj, Fiorinda; Karri, Padmavathi V.; Moody, Wylie; Brown, Alexandria; Patel, Anisha B. (Frontiers in Allergy, 2023)
Immune checkpoint inhibitors (ICIs) have revolutionized cancer therapy. Since the approval of ipilimumab in 2011, a total of nine ICIs have gained indications for various solid and hematologic malignancies. The expanding use of ICIs in oncology underscores the need for diagnosis and treatment expertise in immune related adverse events (irAE). Cutaneous toxicities are the earliest and most common irAE in this class of therapy. In addition to the more frequent reactions including vitiligo, lichenoid dermatitis, psoriasiform dermatitis, other less common skin toxicities including bullous dermatoses, neutrophilic dermatoses, and autoimmune dermato-rheumatologic diseases have been reported. Even though less than 3% of cutaneous irAEs (irCAEs) are classified as grade 3 or higher events, irCAEs can greatly impact quality of life. Appropriate management of irCAEs is critical to avoid unwarranted interruptions or discontinuation of lifesaving immunotherapy.